Banana Production Trends, Cultivar Diversity, and Tissue Culture Technologies Uptake in Kenya - Caroline N. Wahome; John M. Maingi; Omwoyo Ombori; Jacinta M. Kimiti; Ezekiel M. Njeru (International Journal of Agronomy)
Banana (Musa acuminate L) is the world’s most widely known and distributed fruit and is a great contributor to food security in the developing world. However, many limiting factors affect banana farming, which cut across sociodemographic factors and agronomic and management practices. The current study was carried in three counties, including Kisii, Nyamira, and Embu. The study aimed to assess agronomic practices, banana production practices (main banana cultivars, source of planting materials), market information, and awareness of tissue culture bananas. Sample size was determined using the Snedecor and Cochran formula, and data were collected using structured questionnaires, observation, and face to face interviews from 90 smallholder farmers. Data obtained were analysed using Statistical Package for Social Sciences (SPSS) version 22.0, and Microsoft Excel was used to generate tables and graphs. Results indicated that banana production in Kisii, Nyamira, and Embu were limited by several factors including pests and diseases, limited access to quality disease-free planting materials, access to extension services, especially in Kisii and Nyamira, as well as access to agrochemicals. Declining production as well as limited market access also adversely affected production in these regions. Most farmers chose cultivars according to the availability of planting materials, suitability to the region, productivity, as well as market demand. The most predominant cultivar in Kisii and Nyamira was the Ng’ombe which was planted by about 90% and 73.3% of the respondents, respectively. In Embu, the most common cultivar was Israel and was planted by 96% of the respondents. More than 50% of the farmers in Kisii, Nyamira, and Embu cited lack of awareness of tissue-cultured bananas. None of the respondents in the study sites carried out any value addition processes on bananas thus limiting exploitation of a major revenue source. There was low adoption of tissue-cultured banana cultivation with the highest recorded number of respondents growing tissue-cultured banana reported in Embu (36%), followed by Kisii (10%) and lastly Nyamira (3.3%), as well as limited knowledge of tissue culture technology in three counties with 60% of the respondents in Kisii, Nyamira, and Embu indicating limited knowledge of the tissue-cultured banana varieties. This could potentially lead to a decline in production due to the use of potentially diseased planting materials. Creating awareness with the aid of relevant authorities on the potential benefits of utilizing disease-free tissue-cultured bananas and adopting low-cost tissue culture technology will significantly boost banana production in these regions and the country as a whole. The results of this study could be used by relevant stakeholders to increase banana productivity in the study areas.